Understanding the SARS-CoV-2 Variations and Lineage: Experience Report (Research, Society and Development, 2022)
Given the current global scenario, facing the spread of the new coronavirus, where there was an abrupt advance in contamination, and health professionals needed to carry out a process of adaptation to SARS-CoV-2, both in patient care and with individual care and protocols to avoid contagion. During the pandemic, other variants of the virus were identified as new highly transmissible strains, thus making it necessary to update information.  This is a descriptive study, with a qualitative approach of the experience report type, carried out by nursing students through the implementation of health education, with the objective of assisting the knowledge of a multidisciplinary team about the SARS-CoV-2 variant and thus enable them to act in the new pandemic reality. It was based on Charles Maguerez's methodology of problematizing the Arch of Charles Maguerez, in which the reality of the scenario was observed, key points were surveyed, the theorizing of the subject, possible solution hypotheses and application to reality were carried out. Through of the problem and its specificities, an action in health was carried out, consisting of some steps, there was a conversation circle and through the presentation of the academics, the development of the transfer of necessary information began, with a significant exchange and clarification of the main doubts. With this, the multidisciplinary team was able to better experience and work on behalf of patients with greater responsibility and training, with the certainty that preventive care against the virus is the best form of protection.